Writing and presenting a systematic review emphasizing the Cochrane Handbook for systematic reviews - Fariba Khayyati; Zahra Fathifar; Shayesteh Shirzadi; Tahereh Pashaei (Chronic Diseases Journal, 2016)
BACKGROUND: The systematic review is a scientific method for identifying and presenting early research, quality assessment, and integration of their results. This study aimed to describe the principles of systematic reviews and inscribe related articles emphasizing the Cochrane Handbook, for using of medical and health students.